Foil scrap reduction: Continuous improvement in the foil processing industry - Mgbike, Kingsley (My University, 2020)
The overall objective of the study is to provide insight as to what it takes to reduce scrap levels at a foil manufacturing plant, as well as interpret the essence of Metallizers and addressing the gaps in relation to its vitality within the foil manufacturing process. The invention of Hot Stamp and Cold Stamp foil relate to a pigmentary foil and production method thereof. The pigmentary foil comprises at least one PET membrane base, on which coloring layer material and adhesive layer material are coated orderly (Guoping 2010). The key documents essential for production and reducing pump down times in the Metallizer chambers vary by a significant margin in order to increase production. By creating Pareto charts to establish root cause of scrap accumulation, conducting a Fishbone discussion to brainstorm ideas that would effectively mitigate scrap, and host a TPM Kaizen to exercise all ideas and suggestions enhancing the process, API would be in a better position to improve the quality of the metallizer; boosting its capacity and Overall Equipment Efficiency (OEE).
Keywords: Continuous Improvement; Food Science; Cost savings; Pareto; Overall Equipment Efficiency